L-Asparaginase in Treatment of Acute Leukaemia and Lymphosarcoma. Issue 5690 (24th January 1970) - Beard, M. E. J.; Crowther, D.; Galton, D. A. G.; Guyer, R. J.; Fairley, G. Hamilton; Kay, H. E. M.; Knapton, P. J.; Malpas, J. S.; Scott, R. Bodley
Abstract : L-Asparaginase was used to treat 40 patients with acute leukaemia or lymphosarcoma. Fifteen with acute lymphoblastic leukaemia either untreated or in relapse after previous therapy were given "Squibb, " "Bayer, " or "Porton" L-asparaginase. Five of these patients had complete remission of their disease, and four had good partial remission. Eleven patients with acute myeloid leukaemia were treated for a short period with L-asparaginase alone. None of them went into remission though a pronounced fall in the numbers of circulating white cells was seen. Six patients with lymphosarcoma received L-asparaginase, two of them having good partial remissions. The toxic side-effects of the L-asparaginase from the three sources seemed to vary, and L-asparaginase from Erwinia carotovora appeared to be antigenically different from the enzyme produced by Escherichia coli. The way in which leukaemic cells become resistant to the action of the enzyme requires further investigation. To overcome this resistance asparaginase should be used in combination with other drugs in the treatment of acute leukaemia.